Analysis of quality of life and periodontal health with an eight-unit maxillary fixed retainer through a prospective clinical trial - Mohamed H. Abbas; Essam M. Abdalla; Nadia M. El Harouni; Eiman S. Marzouk (Scientific Reports)
Abstract Retention is crucial in orthodontics, aiming to preserve treatment outcomes and enhance patient satisfaction with permanent fixed retainers. However, a removable retainer may be needed with fixed retainers to prevent unwanted changes. An eight-unit extended fixed retainer is proposed to eliminate the need for a removable retainer, addressing the undesired changes associated with six-unit fixed retainers. The impact of extended retainers on periodontium and quality of life remains unexplored. This study evaluates the periodontal response and patient-reported quality of life with an eight-unit maxillary fixed retainer. A single-arm prospective clinical trial with only twenty-eight test group patients (6 males, 22 females) who finished active orthodontic treatment were recruited. The mean age was (19.8 ± 4.5 years). This research was approved by the institutional review board of the Faculty of Dentistry, Alexandria University (IORG:0008839, No-0479-8/2022). The registration date of this study was (5/06/2023). An eight-unit maxillary fixed retainer was bonded to the palatal surface of the maxillary incisors, canines, and first or second premolars directly after debonding the brackets. The periodontal assessment and quality of life were carried out through clinical examination and valid questionnaires and the patients were followed up for 12 months. The periodontal response improved significantly at 1-year follow-up. The Probing depth, Gingival index, Plaque index, Bleeding index, and mobility index were significantly lower in these patients. Quality of life was assessed by the OHIP-14. The mean score decreased by -1.86 (SD = 4.19), and the acceptance of the orthodontic appliance scale score increased by 0.68 (SD = 0.86), which was significant with a p-value < 0.001. For 12 months of follow-up, an eight-unit maxillary retainer did not adversely affect the periodontal ligaments. meets patients’ expectations and maintains a high quality of life.